Moderation of Leverage on Institutional Ownership to Profitability and Stock Return - Michelle Sabatamia; Harlyn L. Siagian (Budapest International Research and Critics University, 2022)
This study aims to analyze the effect of Institutional Ownership on Profitability and Stock Return with Leverage as the Variable Control. The sample used is secondary data from the Indonesia Stock Exchange (IDX) Annual Report, which Food and Beverages Companies listed on the Indonesia Stock Exchange in 2017-2019. The samples were selected using purposive sampling methods and sample that meets the criteria. This study uses t-test, F-test, and Moderated Regression Analysis (MRA). The proxy used for Profitability is Return on Assets (ROA) and the proxy used for Leverage is Debt to Equity Ratio (DER). These results indicate that partially the Institutional Ownership and Leverage does not effect on ROA and Stock Return, and simultaneously Institutional Ownership and Leverage does not effect on ROA and Stock Return. While Leverage can be the moderating variable between Institutional Ownership on Profitability and Institutional Ownership on Stock Return proven by the increase in the value of R-Square.